(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
The purpose of the following article is to show the changes suffered by the notions of dissimulatio and simulatio during the Baroque period. Specifically, my intention is to illustrate, through the works of Gracian and Accetto, how these rhetorical figures become ways of confronting life.